Minnesota Junior College Faculty Interests and Concerns, Report of a Conference of Instructors in the Humanities (Minneapolis, January 14-16, 1968) - Minnesota Univ., Minneapolis; Moen, Norman W.; Stave, Ramon L.; Minnesota Univ., Minneapolis ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
This conference, on the importance of the humanities in a society that is becoming more urban, youthful, and leisured, noted that humane ideals must not be lost in the quest for technical expertise. Junior colleges, relatively free from academic tradition, can respond to this expectation. The objectives of this conference were (1) to foster an esprit de corps among the teachers, (2) to encourage an exchange of ideas on junior college functions, (3) to coordinate attacks on common problems, (4) to direct university resources to these needs, and (5) to set a precedent for future and continuing discussion, especially on curriculum and instruction. The opening address for the conference was on the ideals, myths, and realities of the junior college mission. Six groups discussed the following: (1) faculty attitudes to liberal arts education, (2) the ideal junior college and its aims, (3) junior college as an institution and its relationship to other institutions of higher education, (4) the role the teacher plays or should play in educating the heterogeneous student body, (5) the uniqueness of the junior college and its problems, and (6) a summary of the questions, problems, and recommendations, with suggestions for further study, as revealed by these discussion groups. Recommended was the establishment of (1) a way to evaluate the junior college and its individual disciplines and (2) intercollegiate programs that would use resources more effectively. (HH)
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Conferences; Educational Objectives; Humanities Instruction; Liberal Arts; Two Year Colleges; Minnesota